Adrenal tumours: how to establish malignancy. (23rd December 2014) - Toogood, Vanita; Milliken, Sam; Morey, Adrienne; Samaras, Katherine
Abstract : Adrenal masses are commonly found in the course of abdominal investigations and present diagnostic challenges. The foremost issue is whether the mass is the cause of the symptoms being investigated. Additional important clinical questions are: (1) is the adrenal mass benign or malignant and (2) whether the adrenal mass is functional or non-functional? We present a case of a 48-year-old man with severe abdominal pain. Imaging revealed a very large adrenal mass. Differential diagnostic procedures were performed and a diagnosis of primary adrenal lymphoma, an extremely rare cause of adrenal malignancy, was made. He proceeded to chemotherapy with cyclical cyclophosphamide, doxorubicin, etoposide and prednisolone, in addition to rituximab. This case illustrates the importance of establishing the nature of adrenal masses, to rapidly facilitate appropriate treatment.